Edukasi Kesehatan Sebagai Upaya Peningkatan Pengetahuan Ibu Hamil dan Kesehatan Balita - Nuraida, Ida; Putri, Devia Lydia (TAAWUN, 2024)
The purpose of this service is to improve the community’s knowledge about the health of pregnant women and toddlers in Cibinong through a health education program. The service methods included an initial survey to measure the community’s level of knowledge on the issue, conducting a needs analysis to determine the focus of the program, and creating educational materials tailored to local needs. This service is carried out by counseling or education methods related to maternal and toddler health. The service showed that the knowledge of pregnant women and the health practices of children under five had improved. The success of the program was enhanced by active community participation and close collaboration with local parties. To transform the community towards the best health, new awareness is essential. This service led to the conclusion that health education is an effective method to increase awareness of pregnant women and toddler health in Cibinong. The program has a positive impact on the community as a whole, in addition to changing one person. Therefore, to improve the well-being of pregnant women and children under five at the community level, health education methods need to continue to be supported and expanded.